2016
DOI: 10.17221/182/2015-swr
|View full text |Cite
|
Sign up to set email alerts
|

Labile forms of carbon and soil aggregates

Abstract: Tobiašová E., Barančíková G., Gömöryová E., Makovníková J., Skalský R., Halas J., Koco Š., Tarasovičová Z., Takáč J., Špaňo M. Soil organic matter (SOM) plays an important role in the soil aggregation and vice versa, its incorporation into the soil aggregates is one of the mechanisms of soil organic carbon stabilization. In this study the influence of labile carbon fractions on the fractions of dry-sieved (DSA) and wet-sieved (WSA) macro-aggregates and the relationship between the content of total organic carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Therefore, stable MaAs would also contain some additional organic matter (Figure 6d). Tobiašová et al [35] indicated the similar outcomes with our results by evaluating LOC (WEOC and ROC) in the aggregate with different sizes. Based on our results, the RSOC seems to be transformed into MBC fraction obviously in MaAs and MeAs, 2021, 9, 1431 which implied that the susceptible fresh OM might be occluded during formation process of larger aggregates.…”
Section: Effects Of Biochar On the Formation Of Soil Aggregatessupporting
confidence: 90%
“…Therefore, stable MaAs would also contain some additional organic matter (Figure 6d). Tobiašová et al [35] indicated the similar outcomes with our results by evaluating LOC (WEOC and ROC) in the aggregate with different sizes. Based on our results, the RSOC seems to be transformed into MBC fraction obviously in MaAs and MeAs, 2021, 9, 1431 which implied that the susceptible fresh OM might be occluded during formation process of larger aggregates.…”
Section: Effects Of Biochar On the Formation Of Soil Aggregatessupporting
confidence: 90%
“…These increases in HWC, microbial biomass and respiration potential were correlated to the soil organic matter content, which was 37% higher under Eucalyptus compared to potato and fallow land uses (Coca-Salazar et al 2021a). Moreover, the absence of soil physical perturbation (Eucalyptus soils are not managed after seedling plantation) could also favour the formation of new aggregates and the binding of the already existing free macroaggregates, microaggregates and silt + clay (Tisdall and Oades 1982;Tobiašová et al 2016). The observed higher soil aggregate stability in water under Eucalyptus is also generally explained by higher soil C content (Wei et al 2006) and a more active microbial community, which is considered to be the consequence of successful afforestation (Caravaca et al 2002).…”
Section: Land Use Effects On Soil Aggregates Toc Tn Concentrations An...mentioning
confidence: 99%
“…Understanding the link between soil C, microorganisms and soil aggregates under different land uses is essential to shed light on the consequences of modifications in soil structure for soil organic matter dynamics and the potential resulting effects on nutrient availability and biogeochemical cycles. Indeed, increased relative abundance of mega-and macroaggregates indicate higher labile carbon content, soil porosity, oxygen diffusion, water infiltration, root penetration and decreased risk of erosion (Whalen and Chang 2002;Pagliai et al 2004;Tobiašová et al 2016). Higher abundance of mega-and macroaggregates is thus generally linked to increased rates of biological processes and higher nutrient availability (Cai et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobiašová [46] similarly conducted a study on labile carbon content in different aggregate sizes and results revealed that macro-aggregates having size 0.25-1 mm had a maximum fraction of labile C especially labile C oxidizable with KMnO4. The aggregate fraction of size 0.5-1 mm was in a negative correlation with labile C fraction and appears to be a crucial indicator of changes in the ecosystems.…”
Section: Kmno4-cmentioning
confidence: 99%